Accessing Powerful Knowledge: A Comparative Study of Two First Year Sociology Courses in a South African University - Sebidi, Kgaugelo; Morreira, Shannon (Critical Studies in Teaching and Learning, 2023)
This paper presents a case study of two first year sociology courses run at an elite South African university in order to speak to student perspectives on the sociology curriculum. The paper provides a comparative analysis of the academic experiences of extended degree (ED) students registered on two first year courses, one of which drew on literature and sociological theory which was mainly Euro-American in origin, and the other of which attempted to situate sociological theory within local contexts. In so doing, it contributes to debates on the role of identity in teaching sociology. We highlight the tension that occurs between the need to make content accessible and relevant for students – particularly for first generation students – and the need to also give students access to the powerful knowledge (Young, 2009) that comes with familiarity with the theory-dense sociological canon.